Control of the Folding Dynamics of Self‐Reconfiguring Magnetic Microbots Using Liquid Crystallinity. (20th January 2020) - Shields, C. Wyatt; Kim, Young-Ki; Han, Koohee; Murphy, Andrew C.; Scott, Alexander J.; Abbott, Nicholas L.; Velev, Orlin D.
Abstract : Reconfigurable microdevices are being explored in a range of contexts where their life‐like abilities to move and change shape are important. While much work has been done to control the motion of these microdevices by engineering their geometry and composition, little is known about their dynamics in complex fluid environments with non‐Newtonian rheology. Herein, it is shown how the actuation dynamics of reconfigurable microdevices made by assembly of patchy magnetic microcubes, which are referred to as "microbots, " can be modulated by their interactions with the anisotropic viscoelastic environment of a liquid crystal (LC). The free energy arising from the elastic strain of LC and formation of topological defects around the microbots influences their folding dynamics, which can be tuned by tailoring both the far‐field orientation of the LC and the local ordering of the LC at the microbot surfaces. These findings represent a first step toward establishing a general set of design rules to control the dynamics of microbots using complex anisotropic fluids. Abstract : Herein, it is shown how the folding dynamics of magnetically actuated microbots can be regulated in liquid crystal (LC) medium. Free energy arising from the elastic strain of LC and topological defects formed around the actuators can be tuned by surface modifications to program microbot dynamics in complex fluids, including foams, gels, blood, and mucus.